Studi Pemanfaataan Teknologi Hydrogen Fuel Cells (HFCs) pada Kapal Peti Kemas - Muhammad Dihan Ramadhan Pradana; Setyo Nugroho; Eka Ardhi (Rekayasa, 2023)
International Maritime Organization has previously issued an ambitious strategy to decrease maritime carbon emission by by 70% in 2050. There are lots of alternatives in reducing carbon emission, with hydrogen fuel cells being one considered. Hydrogen fuel cells (HFCs) is projected to decrease maritime carbon emission up to 80% and has larger engine efficiency, roughly 10-20% higher than of diesel engine. In this research, feasibility analysis of HFCs was conducted through life cycle analysis and simple additive weighting by considering 4 types of fuel (green/blue/gray hydrogen and LNG) and 3 types of HFCs (PEMFC, MCFC and SOFC). Life cycle analysis showed that combination of Solid Oxide Fuel Cells and blue hydrogen came out as the best solution to reduce carbon emission up to 82% for hybrid-powered vessels. From financial perspective however, hybrid-engine option may reduce overall gross income by 27% since it requires higher engine space. Furthermore, utilization of fuel cell resulted in a lower net present value as a result of higher investment cost compared to diesel-powered vessels.